2020
DOI: 10.1371/journal.pone.0232039
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analysis of ARF transcription factors in Brassica juncea var. tumida

Abstract: Auxin signalling is vital for plant growth and development, from embryogenesis to senescence. Recent studies have shown that auxin regulates biological processes by mediating gene expression through a family of functionally original DNA-binding auxin response factors, which exist in a large multi-gene family in plants. However, to date, no information has been available about characteristics of the ARF gene family in Brassica juncea var. tumida. In this study, 65 B. juncea genes that encode ARF proteins were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
4
1
Order By: Relevance
“…Phylogeny and synteny analysis revealed that both the segmental duplications and whole-genome duplications contributed to PtrARF gene family expansion. However, it was somewhat inconsistent with the previous conclusion that segmental duplication was the major cause for the ARF gene family expansion [49][50][51].…”
Section: The Increasing Numbers and Phylogenetic Relationships Of Ptr...contrasting
confidence: 72%
See 1 more Smart Citation
“…Phylogeny and synteny analysis revealed that both the segmental duplications and whole-genome duplications contributed to PtrARF gene family expansion. However, it was somewhat inconsistent with the previous conclusion that segmental duplication was the major cause for the ARF gene family expansion [49][50][51].…”
Section: The Increasing Numbers and Phylogenetic Relationships Of Ptr...contrasting
confidence: 72%
“…In addition, the percentage of CTD-truncated PtrARF (37.5%) was higher than that in Vitis vinifera (10.5%) [14], A. thaliana (17.39%) [15], O. sativa (24%) [9], Brassica rapa (22.6%) [51], and Solanum lycopersicum (28.6%) [56] but lower than that in Hordeum vulgare (45.0%) and M. truncatula (60.9%) [12,57]. It has been reported that the truncated ARF proteins without CTD function, whose activities were regulated through interaction with other transcription factors instead of interaction with Aux/IAA, are likely to be insensitive to auxin [4,8].…”
Section: The Diversities Of Ptrarf Proteinsmentioning
confidence: 86%
“…The functions of ARFs have been studied in Arabidopsis thaliana , tomato ( Solanum lycopersicum ), papaya ( Carica papaya L.), sugar beet, peach, and other plant species [ 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. AtARF 2 , 3 , 5 , 6 , 7 , 8 , 17 , and 19 regulate apical bud formation, pollen wall synthesis, vascular bundle development, hypocotyl tropic movement, and adventitious root formation [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of PkorARF members lacking CTD domains in Korean pine (38.5%) is higher than that in other species, such as Arabidopsis (17.39%) [ 10 ], tomato ( Solanum lycopersicum ) (28.6%) [ 59 ], Brassica juncea var. tumida (22.6%) [ 60 ], and Populus (37.5%) [ 12 ]. However, the proportion of structural domains lacking in PkorARF (38.5%) is similar to that of PtrARF (37.5%), suggesting both variability in structure among different species and similarity in structure among closely related species.…”
Section: Discussionmentioning
confidence: 99%